ETHICAL CHARACTERISITICS AND REQUIRED FEATURE OF MASS COMMUNICATION STUDENTS IN DIGITAL ERA - Papattha, Chantana (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
The purpose of the study was to study the ethical characteristics and necessary characteristic of mass communication students in the digital era. The qualitative research was conducted with in- depth structured interview from the 16 experts who were experienced in the field of mass media for more than 10 years including lecturers and mass communication officers. Data were analyzed by synthesized table and descriptions. The results showed that: The 20 ethical characteristic of mass communication students in the digital era are self- responsibility and social responsibility, good consciousness, public consciousness, role of self- awareness, sacrifices, do for the collective, social context understanding, receptive, respect and accept of others’ opinions, understanding conflict, respect each other, recognition of differences, good person (right or wrong), respect human rights, respect yourself, present truth, politeness and etiquette, propriety, ethics of information technology, and media literacy. Similarly, the 7 necessary characteristic of mass communication students in the digital era are seek knowledge, analytical and synthesis thinking, critical thinking, creative thinking, writing and communication skills, interdisciplinary, multitasking.